Microstructure and tensile properties of AISI 410 stainless steel welded TIG method - CALIK, Adnan; UCAR, Nazim (International Journal of Computational and Experimental Science and Engineering, 2023)
In this study, the weldabilities, microstructures and tensile properties of AISI 410 stainless steel joints fabrication by tungsten inert gas (TIG) welding method were investigated. TIG welding was carried out on steels by using welding wire ER 410 (AWS A5.9) 2.8 mm in diameter. Tensile test results showed that while tensile and yield strength increased, the elongation value decreased significantly. The yield strength and tensile strength were measured as 619 and 801 MPa after welding process, respectively. In addition, the failure location occurred without any significant cross-sectional narrowing. Microstructure investigations have been carried out using optical microscopy and Scanning Electron Microscopy (SEM). The obtained results indicated that the microstructure of weld metal region had a dual phase such as martensite and ferrite.